PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SIMULASI MENGGUNAKAN VISUAL STUDIO CODE UNTUK MATA PELAJARAN FISIKA MATERI FLUIDA DINAMIS DI SEKOLAH MENENGAH ATAS - Rahimi, Futri Hakiki; Palloan, Pariabti; Yusuf, Momang; Pasarai, Teguh Wibawa (EduFisika: Jurnal Pendidikan Fisika, 2026)
This study aims to create and assess simulation-based learning media utilizing Visual Studio Code for creating dynamic fluid materials at the high school level. This development is centered on students’ misconceptions and the shortcomings of pre-built simulation platforms such as PhET and discontinued technologies (e.g., Adobe Flash). In contrast to previous studies, this research focuses on the development of an entirely customizable web-based simulation, created with HTML, CSS, and JavaScript. The simulation allows for teacher customization, access on multiple devices (responsive design), and offers the integration of interactive worksheets. The development of the simulation learning media was performed through the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Construct validity analysis showed that most items were positively correlated with the total score, while reliability testing yielded a Cronbach’s Alpha of 0.576, indicating the need for further instrument refinement. The evaluations made by students and teachers were classified as very good, indicating high acceptance and high practicality. This study is limited to evaluating media feasibility and media practicality, without evaluating the effect of media on student’s learning outcomes and conceptual understanding. The results of this study concluded that the media is feasible and practical to provide support for interactive conceptual visualization in physics learning. Future studies are needed to evaluate the effectiveness of the media through an experimental or quasi-experimental design.